Hypoglycemia in Type 2 Diabetes: Current Controversies and Changing Practices - Bloomgarden, Zachary; Einhorn, Daniel (Frontiers in Endocrinology, 2012)
Hypoglycemia is well-recognized to limit the degree of glycemic control possible for many individuals for diabetes. Although the likelihood of hypoglycemia increases as A1c levels decrease in type 1 diabetes, insulin-treated type 2 diabetic persons with higher A1c appear paradoxically to have more hypoglycemia; this may in part explain the adverse outcome reported in the ACCORD study. Approaches to glucose-lowering causing lesser degrees of hypoglycemia, technologies to better ascertain hypoglycemic events, and better understanding of patient characteristics associated with greater likelihood of hypoglycemia will all be required to reduce this limiting factor in optimizing glycemic treatment.